Modeliranje prometnih procesa u telekomunikacijskim sustavima - Begović, Mladen; Šarić, Slavko; Mikula, Miroslav (Promet - Traffic&Transportation, 2012)
Modelling of traffic processes in telecommunication systemsin the process of the shift of technologies is indispensablefor purposes of planning and designing the extension of capacitiesand monitoring of the existing traffic flows. The paperdeals with the traffic problem in the telecommunication systemin the period of the exchange of technologies, discussing trafficas a random process and expounding the need for modellingtraffic processes by way of servicing models.